Inclusive Growth, Educational Attainment and Morbidity Rate in Papua Province - I Gede Agus Ariutama; Anisa Fahmi (Economics Development Analysis Journal, 2019)
This study aims at determining inclusive growth and exploring the relationship between inclusive growth, educational attainment and morbidity rate in Papua province. This is due to the fact that Papua Province with special autonomy status attempts to catch up with economic growth from other provinces and increases income equity by focusing on education and health. This study exploits Social Mobility Curve (SMC) and Panel VAR to comprehend inclusive growth and determine the reciprocal relationship between Social Mobility Index, average years of schooling and morbidity rate in Papua Province in 2011-2016. Based on the results, there was economic growth in Papua Province which was still accompanied by an increase in income disparity, thus, it could be concluded that economic growth in Papua was still not inclusive. Regarding the results of the Panel VAR, there was no reciprocal relationship between the three variables with education and health having a positive and significant effect on inclusive growth. The positive influence of education and health is probably due to individual productivity and globalization factors. To increase inclusive growth, Papua Province is advised to improve student education so that later students most likely be more productive and get better jobs and salaries.